(untitled) (Journal of Geography and Environmental Management, 2016)
The anthropogenous factor is included, now, into number of leading factors of formation of ecological-geomorphological environment of active mountain-industrial development, including territory of the Central Kazakhstan. This factor defines spatial distinctions of an orientation, the maintenance and intensity exodynamic processes. Character and degree of danger of these processes should be considered at ecological-geomorphological division into districts applied directivity.